RGD peptide doped polypyrrole film as a biomimetic electrode coating for impedimetric sensing of cell proliferation and cytotoxicity - Yuan, Li; Chao, Yu (Journal of Applied Biomedicine, 2017)
A novel and facile in vitro cell sensing system has been developed with one-step electropolymerization of the conducting polypyrrole(PPy) polymer using RGD peptide as the sole dopant on an indium tin oxide (ITO) surface. The resulted RGD peptide-doped polypyrrole (PPy/RGD) composite film had a robust surface, in which PPy provided a biocompatible matrix for cell growth and a conducting interface for electrical detection, while the RGD peptide entrapped in the PPy matrix conferred the desired biomimetic properties. Using the human lung cancer cell A549 as a model, this system can be used to monitor cell behaviors of proliferation and cytotoxicity.
Keywords: Microscopy, Electrochemical, Scanning; polypyrrole; Biosensing Techniques; Oligopeptides; skenovací elektrochemická mikroskopie; Antineoplastic Agents; pyrroly; biosenzitivní techniky; proliferace buněk; oligopeptidy; polymery; biomimetické materiály; Pyrroles; elektropolymerizace; Polymers; Cell Proliferation; protinádorové látky; Biomimetic Materials; RGD peptidy